Interrelationship Analysis of Geopolymer Components using Pearson Correlation Technique - Kusbiantoro, Andri; Norbaizurah, Rahman; Noor Fifinatasha, Shahedan (Trans Tech Publications, Switzerland, 2014)
Performance of geopolymer based specimens is significantly affected by internal and external aspects. Curing temperature and air humidity are among the prominent external factors that contribute to the alteration of geopolymer properties. Nevertheless, internal component of geopolymer binder also carries essential effect to the hardened geopolymer binder produced. In this research, the study was concentrated on the elemental composition of source material components and their interrelation to the performance of geopolymer binder produced. Different types of fly ash were used as the source material in this research. Low calcium (class-F) fly ash was combined with high calcium (class-C) fly ash to determine the elemental composition effect, particularly SiO2, Al2O3, and CaO to the geopolymer properties. Analysis using SYSTAT statistical software indicated the importance of oxide composition of source material to the geopolymer specimens produced. Initial setting time of geopolymer paste was also possibly important to the compressive strength of geopolymer specimens produced. Nevertheless, final setting time indicated less importance to the compressive strength development of geopolymer binder.